Trends in breast cancer surgery at Brazil's public health system. Issue 5 (6th February 2017) - Freitas‐Júnior, Ruffo; Gagliato, Debora Melo; Moura Filho, João Wesley Cabral; Gouveia, Pollyana Alves; Rahal, Rosemar Macedo Sousa; Paulinelli, Régis Resende; Oliveira, Luis Fernando Pádua; Freitas, Paola Ferreira; Martins, Edesio; Urban, Cicero; Lucena, Clécio Ênio Murta
Abstract : BACKGROUND AND OBJECTIVES: To analyze time trend patterns in Breast Cancer (BC) surgeries performed at Brazil's Public Health System, known as SUS from 2008 to 2014. METHODS: Ecological study of time series, based on the database system from SUS. Information on surgical procedures performed for BC treatment was collected. Analysis of the absolute number of surgeries was performed using Poisson Regression through Jointpoint Regression, and the trends were calculated through the annual percentage change (APC), with a confidence interval (CI) of 95%, and statistical significance when P  < 0.05. RESULTS: Data analysis from 193.596 breast surgeries revealed a reduced number of simple mastectomies (APC −4.4%; CI −7.4 to −1.4; P  < 0.05); stable trends in radical mastectomy with lymphadenectomy (APC −1.0%; CI −2.4 to 0.5; P  = 0.1) and breast conserving surgery (APC 0.4%; CI −1.6 to 2.4; P  = 0.6). Also, we observed a reduced number of axillary lymphadenectomy dissection (APC −16.8%; CI −26.8 to −5.4; P  < 0.05); increased trends in breast reconstruction with implants after 2011 (APC 9.1%; CI 0.1‐18.8; P  < 0.05) and with flaps after 2012 (APC 61.3%; CI 41.3‐84.0; P  < 0.05). The overall rate of patients with breast reconstruction increased from 15% in 2008 to 29.2% in 2014. CONCLUSIONS: We found a significant increase in breast reconstruction in public health system in Brazil, and also a reduction in simple mastectomy and axillary lymphadenectomy.